2016
DOI: 10.5455/ijmsph.2016.0108201581
|View full text |Cite
|
Sign up to set email alerts
|

Study to assess the extent of maternal health care utilization by women residing in urban slum area in Ahmedabad

Abstract: Background: Maternal mortality is on an average 18 times higher in developing countries as compared to developed countries. Despite the existence of many national programs for improving maternal and child health, maternal mortality and morbidity continue to be at higher side, at an unacceptable level. Objective: (1) To know the extent of maternal health care utilization; (2) To study the factors affecting utilization of maternal care services. Materials and Methods: The cross-sectional study was conducted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Utilization of individual ANC services such as ANC registration in the first trimester (74.6%), Td injections (100%), more than four ANC visits (82.6%), and IFA tablet (4) consumption was more than the national coverage survey . Our study concluded that mother's education has a significant association with the utilization of ANC services, which is (8,11) similar to other study findings .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Utilization of individual ANC services such as ANC registration in the first trimester (74.6%), Td injections (100%), more than four ANC visits (82.6%), and IFA tablet (4) consumption was more than the national coverage survey . Our study concluded that mother's education has a significant association with the utilization of ANC services, which is (8,11) similar to other study findings .…”
Section: Discussionsupporting
confidence: 90%
“…In our study, there were 119 (94.5%) institutional deliveries, which is very encouraging. However, around 5.6% of them were delivered (8) at home. Another study conducted by Patel et al found 8% home delivery in an urban slum; both are much higher than the state's NFHS-5 report (2019-2020), of 1.1%, which is a (5) cause of concern .…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Utilization of reproductive health services is in turn related to their availability and socio-economic, demographic and cultural factors such as women's age, education, employment, caste and autonomy. [13][14][15][16][17] ( Access to health care facilities in terms of distance and who provided health care are major factors that influenced utilisation of services. Apart from above all factors women's autonomy is also a major determinant of utilization of maternal and child care services, women with greater freedom of movement are more likely to utilize antenatal and delivery care.…”
Section: Introductionmentioning
confidence: 99%
“…9,[23][24][25] Obstetrik şiddet maruziyeti; kadınların sağlık kuruluşunu kullanmaktan kaçınmasına ve/veya sağlık kuruluşuna başvurmayı ertelemesine, kadınların üreme yaşamları konusunda olumsuzluklara, çocuk sahibi olma isteğinin azalmasına, hamile kalma ve doğum yapma ve doğum şeklini seçme korkusuna ve postpartum depresyona neden olabilmektedir. 14,[26][27][28][29][30][31] Kadın hakları aktivisti yazarlar ise konunun kadın hakkı ihlali ve cinsiyete dayalı bir kavram olduğunu, yapısal bir şiddet içerdiğini, mağdur-fail arasında bir güç eşitsizliği söz konusu olduğunu belirterek, konunun obstetrik şiddet adı altında ele alınması gerektiğini savunmaktadırlar. 10,23,25,32 Ülkemiz literatüründe obstetrik şiddet konusunda yapılmış çalışma sayısı çok azdır ve bu çalışmalarda "obstetrik şiddet" terimi kullanılmıştır.…”
Section: Adlandirma Tartişmalariunclassified